Analisis Vienna Convention 1969 Mengenai Ketentuan Pembatalan, Pengakhiran dan Penundaan Atas Suatu Perjanjian Internasional - Fidelia Fidelia; Syahmin Awaludin Koni; Dedeng Zawawi (Jurnal Ilmiah Penegakan Hukum, 2019)
In the 1969 Vienna Convention on International Treaties, the provisions concerning the conditions for suspension, invalidity, termination of an international treaty turned out to contain provisions exceeding one third or 40 percent of the total number of the total Convention as many as 31 articles out of 85 articles starting from article 42 to article 72. where the provisions -these provisions have led to disputes and differences of opinion so that consensus is difficult to achieve at the time. This study aims to reveal the background or reasons why so many provisions regarding suspension, invalidity, and termination in the 1969 Vienna Convention are needed that can actually reduce the binding power of international treaties. This research is a normative juridical study, and is analytical descriptive. After careful research, it was found that the International Law Committee which formulated this convention had deliberately arranged it in such a way that it would cancel, terminate or suspend the implementation of an international treaty, no longer looking for reasons other than based on the reasons specified in The 1969 Vienna Convention.